Análise morfológica e cefalométrica de pacientes diagnosticados com síndrome da apneia obstrutiva do sono - PEREIRA, Amanda Letícia Pinto (2018)
Objective: This study is an evaluation of the facial skull growth pattern, pharyngeal air space and position of the hyoid bone of patients diagnosed with OSA, correlating these factors with the variables age, gender and mass index body (BMI), aiming to draw a morphological pattern that is a predictor for the syndrome. Methods: The charts of 26 patients diagnosed with OSAS were used. The cephalometric data found at anteroposterior facial growth, upper and lower and posterior and vertical air space of the hyoid bone. In addition to the cephalometric data, gender, age, BMI, hard palate format and facial pattern were also collected. Results: 50% of the sample was made by men and 50% by women, where the mean age and BMI were 50.5 and 27.8, respectively. Most of the patients had the facial profile and biotype classified as straight and mesocephalic, which characterizes a harmonic profile. However, according to the cephalometric data analysis, 50% of the sample presents a class II mandibular relationship. "Patients may be subjected to some type of alteration in cephalometric data." Conclusion: 1) Obstructive sleep apnea has a strong relationship with genetic alterations, especially when combined with IMC factors elevation and advanced age. 2) Most apneic patients have a class II mandibular relationship. 3) Apneic men aged 60-70 years and overweight tend to have smaller posterior airspace dimension than women. 4) Apneic women between 60-70 years of age are overweight tend to have less dimension of inferior posterior air space when compared to men.